Percepcja jakości produktów żywnościowych przez młodych konsumentów - Matysik-Pejas, Renata (Perception of Foodstuffs Quality among Young Consumers, 2006)
Consumers increasingly pay attention not only to prices of food products but also to their quality. They demand healthy and safe foodstuffs, minimally processed. Also producers who understand market requirements attach more importance to quality of the products they offer. Studies on the importance of quality for young consumers of food reveal that they associate quality first of all with brand and high price. Regarding food with respect to basket of values for consumer, it may be noticed that usability and sensory value have the utmost importance for purchased food products. Purchasers are usually satisfied with the quality of Polish products and highly estimate it in comparison with foreign products.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 80-85